TEACHER PERFORMANCE MANAGEMENT THROUGH PDCA-BASED TEACHING MODULE UTILIZATION TO ENHANCE LEARNING QUALITY IN SENIOR HIGH SCHOOLS: A CASE STUDY AT SMAN 1 NAGRAK AND SMAN 1 CIBADAK, SUKABUMI - Shafhan Jamil, Ilman; Hidayat, Hidayat (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2026)
Teacher performance management is a key driver of improving instructional quality, particularly in secondary schools that must continually adapt to curriculum changes and administrative demands. The teaching module functions as a primary instrument for planning, implementation, evaluation, and reflection within the teaching–learning process. This study examines the implementation of teaching modules as part of teacher performance management at SMA Negeri 1 Nagrak and SMA Negeri 1 Cibadak, as well as the factors that facilitate or hinder their use. The theoretical framework draws on Armstrong’s (2020) performance management theory, Deming’s PDCA cycle of continuous improvement, and educational management approaches that emphasize the strategic role of teachers. This research employs a qualitative case study design using interviews, classroom observations, document analysis, and questionnaires, analyzed through descriptive thematic techniques. The findings indicate that although teachers acknowledge the importance of teaching modules, their implementation in practice remains suboptimal. School monitoring, academic supervision, and teachers’ individual commitment strengthen module utilization, whereas curriculum revisions, limited preparation time, and administrative-driven module development pose significant challenges. Simplifying module formats and providing continuous support from the school have proven effective in improving implementation quality. In conclusion, the effectiveness of teacher performance management through teaching modules depends not solely on policy instruments but also on strong collaboration among teachers, school leaders, and the broader school environment. When implemented adaptively and consistently, teaching modules hold substantial potential to enhance teacher professionalism and improve instructional quality.